Metrópoles justas, democráticas e sustentáveis: uma perspectiva à luz do projeto urbana sobre a gestão de transição de políticas públicas - Traub, Andrea (2024)
The research developed aims to propose recommendations and a framework for public policy transitions for the Metropolis of Curitiba and its metropolitan region, with the aim of promoting a more just, democratic and sustainable metropolis. The case study on the Urban Arenas for Sustainable and Fair Cities (UrbanA), developed in the European context, was used as a basis for identifying successful practices that can be adapted to the reality of the Metropolis of Curitiba. The relevance of the research lies in the practical application of contemporary theories of Transition Management, an approach developed within the scope of the UrbanA project. The analysis highlighted the socioeconomic inequalities of the metropolitan region and the challenges faced by metropolitan governance, proposing strategies that can promote significant changes in this scenario. Among the main recommendations proposed, the promotion of interdisciplinarity and transdisciplinarity, the participation and inclusion of civil society, and the co-creation and collaboration between different actors, including government, academia, the private sector and non-governmental organizations, stand out. These recommendations are seen as fundamental to addressing complex urban challenges and promoting more inclusive and effective governance. The proposed transition framework suggests the adoption of innovative and flexible practices that allow for the continuous experimentation and adaptation of integrated, inclusive and more effective public policies. Environmental sustainability is treated as a central principle, emphasizing the importance of respecting ecological limits and preserving natural resources. The implementation of continuous monitoring and evaluation systems is recommended to ensure that initiatives are on track and can be adjusted as necessary. The research concludes that, in order to achieve a sustainable and equitable transformation in the Metropolis of Curitiba, it is essential to integrate the active participation of civil society, interdisciplinarity, innovation, and transparent and collaborative governance. These elements are seen as fundamental to the creation of a metropolis that benefits the entire population, promoting social justice and democracy, in addition to ensuring a more sustainable and resilient urban future. For future work, it is suggested to carry out comparative studies between different metropolises that have implemented Transition Management, analyzing the impacts and results obtained in different contexts. Another relevant aspect for future research is the longitudinal analysis of the impacts of implemented public policies, using performance indicators and participatory evaluations to monitor progress and identify improvements.